Lactic Acid Bacteria (LAB) from Fermented Milk Leftover for Wastewater Treatment of Soybean-Based Industries - Trimulyono, Guntur; Isnawati; Asri, Mahanani Tri; Khaleyla, Firas (Hasanuddin University, 2023)
Tempeh and tofu are widely consumed by Indonesians and easily made using simple tools and method, thus numerous home industries producing are emerging. However, soybean processing in these industries produces high volume of wastewater. This study provides a simple wastewater treatment instrument design that could be used by soybean-based home industries by applying a series of physical, chemical, and biological treatment. Physical treatment was performed by filtration, chemical by addition of alum salts, while biological treatment was done by supplementing with lactic acid bacteria (LAB) from leftover container of fermented milk. Wastewater was recorded by its parameters (temperature, pH, dissolved oxygen/DO, biological oxygen demand/BOD, turbidity) at every phase of treatment after incubation for two various of periods; 1 hour and 5 days. Results showed that wastewater treated using instrument design had changes in all of its parameters observed during the course of treatment. Wastewater treated in all phase of instrument incubated for 1 hour showed parameters approaching wastewater quality standards, thus it was safer to be disposed to environment compared to wastewater incubated for 5 days. Wastewater treatment as designed in the current study can be applied by soybean-based home industries with short incubation time to remediate wastewater produced during soybean processing before disposal.